THE USE OF CROSSWORD PUZZLE ON THE STUDENTS’ ACHIEVEMENT IN LEARNING VOCABULARY - Tahir, Muhammad; Dwi Payana, Wita; Julkanedi, Julkanedi (Linguistik : Jurnal Bahasa dan Sastra, 2023)
Vocabulary have a big contribution to support the successful students’ of learning English, because without grammar is not big problem in communication, but without vocabulary is large problem in communication with students. It means that vocabulary is very important thing in learning English. This research was conducted the use of crossword puzzle on the students’ achievement in learning vocabulary. The minimum completeness criteria of english lesson SMA Negeri 1 Badar =60. Based on the research mean score of students test on pre test =44,57. The mean score on posttest improved become = 78,04 and it reached the minimum completeness criteria score. There were 33,47 point the difference between pre test to the post test score. The calculation of data by using t test and found the t-observation=3,285 then compared it with ttable=2,074 of level alpha = 5%. It meant that tobservation was higher that t-table =3,2852,074. So, the researcher concluded that there were achievement on student use of crossword puzzle on the Students’ in learning vocabulary on the X students’ of SMA Negeri 1 Badar.